Negative electrode for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, and method for producing negative electrode for non-aqueous electrolyte secondary battery
The use of flaky silicon particles with a silicate binder and conductive agent in the negative electrode of non-aqueous electrolyte secondary batteries addresses the issue of silicon expansion and contraction, improving cycle characteristics and capacity retention through stress alleviation and stable lithium ion conductivity.
Patent Information
- Application Number
- JP2021574039
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-01-26
AI Technical Summary
Existing non-aqueous electrolyte secondary batteries, such as lithium ion batteries, face challenges in maintaining cycle characteristics due to the expansion and contraction of silicon particles used as the negative electrode active material, leading to stress, cracking, and reduced capacity over repeated charging and discharging cycles.
A negative electrode design incorporating flaky silicon particles with a silicate binder and conductive agent, where the silicon particles are stacked in the thickness direction of the mixture layer, with a silicate film covering the particles to stabilize their expansion and contraction, and a conductive agent to maintain conductivity, is employed.
This design significantly improves the cycle characteristics of the battery by reducing stress on the electrode, suppressing cracking, and ensuring stable lithium ion absorption and release, thereby enhancing the battery's capacity retention over multiple cycles.
Smart Images

Figure 0007611485000002 
Figure 0007611485000003 
Figure 0007611485000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode for a non-aqueous electrolyte secondary battery, a non-aqueous electrolyte secondary battery, and a method for producing a negative electrode for a non-aqueous electrolyte secondary battery. [Background technology]
[0002] A non-aqueous electrolyte secondary battery, typified by a lithium ion secondary battery, includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. The negative electrode includes a negative electrode current collector and a negative electrode mixture layer supported on the negative electrode current collector. The negative electrode mixture layer includes a negative electrode active material capable of electrochemically absorbing and releasing lithium ions.
[0003] Patent Document 1 proposes using silicon fine particles formed by pulverizing crystalline silicon as the negative electrode active material of a lithium ion secondary battery. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2015 / 189926 Brochure Summary of the Invention
[0005] 2. Description of the Related Art As electronic devices become more sophisticated, there is a demand for improved cycle characteristics of non-aqueous electrolyte secondary batteries used as the power sources therefor.
[0006] In view of the above, one aspect of the present disclosure relates to a negative electrode for a non-aqueous electrolyte secondary battery, comprising: a negative electrode current collector; and a negative electrode mixture layer supported on the negative electrode current collector, the negative electrode mixture layer including a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, a binder, and a conductive agent, the negative electrode active material including flaky silicon particles, and the binder including a silicate.
[0007] Another aspect of the present disclosure relates to a non-aqueous electrolyte secondary battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte, the negative electrode being the above-mentioned negative electrode.
[0008] Yet another aspect of the present disclosure relates to a method for producing a negative electrode for a non-aqueous electrolyte secondary battery, the method including: a first step of obtaining a first slurry containing an organic dispersion medium and flaky silicon particles dispersed in the organic dispersion medium; a second step of obtaining a second slurry containing a silicate as a binder, a conductive agent, and water; a third step of applying the first slurry to a surface of a negative electrode current collector to form a first coating film containing the silicon particles; and a fourth step of applying the second slurry to a surface of the first coating film to form a second coating film containing the silicate and the conductive agent.
[0009] According to the present disclosure, the cycle characteristics of a non-aqueous electrolyte secondary battery can be improved. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view that typically illustrates a silicon flake particle. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic example of a negative electrode for a nonaqueous electrolyte secondary battery according to an embodiment of the present disclosure. [Diagram 3] FIG. 3 is an enlarged cross-sectional view that illustrates a Y portion of the negative electrode in FIG. [Figure 4] FIG. 4 is a schematic perspective view, with a portion cut away, of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Non-aqueous electrolyte secondary battery negative electrode] A negative electrode for a non-aqueous electrolyte secondary battery according to an embodiment of the present disclosure includes a negative electrode current collector and a negative electrode mixture layer supported on the negative electrode current collector. The negative electrode mixture layer includes a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, a binder, and a conductive agent. The negative electrode active material includes flaky silicon (Si) particles, and the binder includes a silicate. The flake shape includes scaly and oblate shapes.
[0012] In the negative electrode mixture layer containing flaky silicon particles, a conductive agent, and a binder, the use of silicate as the binder significantly improves cycle characteristics. Although the detailed reason is unclear, it is speculated as follows.
[0013] In the negative electrode mixture layer, a plurality of flake-shaped Si particles are filled so as to be piled up in the thickness direction of the negative electrode mixture layer. That is, a plurality of flake-shaped Si particles are deposited with their thickness direction facing the thickness direction of the negative electrode mixture layer. The gaps between the Si particles are distributed in the surface direction of the negative electrode mixture layer. The deposition form of the flake-shaped Si particles is generated by forming a coating film containing Si particles by a doctor blade method or the like during the formation process of the negative electrode mixture layer, and compressing the coating film. In such a negative electrode mixture layer, it is presumed that the stress generated by the expansion and contraction of Si particles during charging and discharging is effectively alleviated, and the isolation of Si particles in the negative electrode mixture layer (especially the surface) due to repeated charging and discharging (expansion and contraction of Si particles) is suppressed.
[0014] On the other hand, silicate is compatible with Si particles (including the silicon dioxide film on the surface of the Si particles), and stable binding between the Si particles during charge and discharge cycles is easily ensured. Silicate is easily soluble in water, and by dissolving silicate in water and using it when preparing the negative electrode mixture layer, the surface of the fine Si particles is easily covered with silicate. In addition, a film of Si particles (a film in which flake-shaped Si particles are deposited in the thickness direction) is formed first, and then silicate is dissolved in water to fill the small gaps between the Si particles in the film. When the binder is CMC, the molecular size of CMC is large, and it swells when it contains water, making it difficult for it to enter the gaps in the film. Furthermore, silicate has good lithium ion conductivity, and even if the surface of the Si particle is covered to some extent with silicate, the absorption and release of lithium ions by the Si particle is smoothly performed through the silicate. In addition, the surface of the flake-shaped Si particle is covered with a silicon dioxide film that is difficult to oxidize, and it is in a state where it is easy to bond with the silicate. This bond is a chemical bond and can withstand the expansion and contraction of the Si particles.
[0015] The above-mentioned effect of the flaky silicon particles and the effect of the silicate combine to significantly suppress the decrease in capacity that occurs with repeated charge and discharge.
[0016] (Flake-shaped silicon particles) The flake-shaped Si particles are preferably nano-level fine particles. The flake-shaped Si particles may have a thickness T of 30 nm or more and 250 nm or less, and a major axis LD of 500 nm or more and 5000 nm or less. When the thickness T is 250 nm or less, the particles are small, so stress is easily relaxed, and cracks caused by the expansion and contraction of the Si particles during charging and discharging are easily suppressed. When the thickness T is 30 nm or more, the strength of the Si particles is easily ensured, and a specific surface area of a moderate size is easily obtained. When the specific surface area is excessively large, the side reaction between the Si particles and the non-aqueous electrolyte becomes excessive, lithium remains on the surface of the Si particles, which may hinder the movement of lithium ions to the positive electrode, and the reaction efficiency may decrease. When the major axis LD is 500 nm or more, the grinding time in the wet grinding process during the preparation of the flake-shaped Si particles can be shortened, which is advantageous in terms of manufacturing costs and productivity.
[0017] From the viewpoint of suppressing cracking due to expansion and contraction of Si particles during charging and discharging, the thickness T may be 200 nm or less, or 150 nm or less, and the major axis LD may be 2000 nm or less, or 1000 nm or less.
[0018] The flake-shaped Si particles may be finer particles having a thickness T of 30 nm or more and 150 nm or less and a major axis LD of 60 nm or more and 300 nm or less. In this case, the finer Si particles tend to suppress cracking during charging and discharging. However, the pulverization time in the wet pulverization process during the preparation of the flake-shaped Si particles tends to be long, which tends to increase costs.
[0019] From the viewpoint of easily packing the Si particles so as to be piled up in the thickness direction of the negative electrode mixture layer, the ratio of the long diameter LD to the thickness T: LD / T (hereinafter also referred to as the aspect ratio) is preferably 2 or more, and more preferably 3 or more. From the viewpoint of easily suppressing breakage of the Si particles, the aspect ratio is preferably 15 or less. The aspect ratio may be 2 or more and 15 or less, or 3 or more and 15 or less. When the aspect ratio is 2 or more and 3 or less, the thickness T may be 30 nm or more and 150 nm or less.
[0020] The thickness T and major diameter LD of the flaky silicon particles can be determined by the following method.
[0021] A scanning electron microscope (SEM) is used to obtain an image of a cross section (cross section perpendicular to the main surface of the negative electrode current collector) in the thickness direction of the negative electrode mixture layer, and it is confirmed that the Si particles are flaky and that the flaky Si particles are packed so as to be stacked in the thickness direction of the negative electrode mixture layer. If it is difficult to distinguish the Si particles, elemental analysis is performed by energy dispersive X-ray analysis. Next, the thickness T and major axis LD of the flaky Si particles are obtained.
[0022] Here, Fig. 1 is a schematic diagram showing a flaky Si particle observed in an SEM image of a cross section in the thickness direction of a negative electrode mixture layer. The maximum distance between two parallel lines L1 and L2 tangent to the contour of a flaky Si particle 20 in the SEM image is determined as the long diameter LD. Furthermore, the distance between two parallel lines L3 and L4 perpendicular to the long diameter LD and tangent to the contour of the flaky Si particle 20 is determined as the thickness T.
[0023] In the above, 50 Si particles are randomly selected from the SEM image of the cross section in the thickness direction of the negative electrode mixture layer, and the long diameter LD of each of the 50 flaky Si particles is measured and their average value is calculated.Furthermore, the thickness T of each of the 50 flaky Si particles is measured and their average value is calculated.
[0024] In a dark field (DF) image of silicon particles taken with a transmission electron microscope (TEM), the ratio of the area of the white part showing crystals to the area of the silicon particles is preferably 20% or less, more preferably 10% or less. In this case, the ratio of the amorphous part having high reactivity with lithium ions is large, and the load characteristics and cycle characteristics are likely to be improved.
[0025] The above area ratio can be determined by the following method.
[0026] In the electron beam diffraction mode of a TEM (JEM-F200, manufactured by JEOL Ltd.), an objective aperture with a diameter of 40 μm is inserted at the diffraction point to obtain a dark field image. Using this image, the ratio of the area of the white part, which indicates the crystalline part in the Si particle, to the total area of the Si particle is calculated. The above area ratio is calculated for each of 30 or more Si particles, and then averaged.
[0027] At least a part of the surface of the flaky Si particles is preferably covered with a silicon dioxide (SiO2) film. The surface of the Si particles is protected by the silicon dioxide film, which suppresses erosion deterioration due to contact of the Si particles with a non-aqueous electrolyte, and improves cycle characteristics. The silicon dioxide film generates lithium silicate and lithium silicide during charging, which makes it easy to increase the initial capacity. In addition, the silicon dioxide film has good lithium ion conductivity, which allows the Si particles to smoothly absorb and release lithium ions.
[0028] From the viewpoint of protecting the Si particles and allowing the Si particles to smoothly absorb and release lithium ions, the thickness of the silicon dioxide film covering the surfaces of the Si particles is preferably, for example, 2 nm or more and 50 nm or less.
[0029] The thickness of the silicon dioxide film can be determined by the following method.
[0030] Using a focused ion beam (FIB) processing device (for example, Hitachi High-Tech Science's FIB-SEM composite device "NX5000"), the acceleration voltage is set to 30 kV, and the cross-section of the negative electrode mixture layer is processed. Then, using a TEM (JEM-F200, JEOL Ltd.), the acceleration voltage is set to 200 kV, and the cross-section of the negative electrode mixture layer is observed. Mapping analysis is performed using energy dispersive X-ray (EDX) analysis to confirm the silicon dioxide film covering the Si particle surface. For the EDX analysis, for example, an analyzer (JED-2300T) manufactured by JEOL Ltd. is used. Using the image from the mapping analysis, the thickness of any 20 points of the silicon dioxide film covering the surface of the Si particle is measured, and the average value is calculated.
[0031] The coverage of the silicon dioxide film on the surface of the Si particles is preferably 3% or more and 30% or less. When the coverage is 3% or more, the erosion and deterioration of the Si particles is easily suppressed. When the coverage is 30% or less, the absorption and release of lithium ions by the Si particles is easily performed.
[0032] The coverage of the silicon dioxide film on the surface of the Si particles can be determined by the following method.
[0033] Using the mapping analysis image obtained by EDX analysis when checking the silicon dioxide film, the total length LA of the outline of the Si particle and the length LP of the part of the outline of the Si particle that is covered with silicon dioxide are calculated. LP / LA is calculated as the coverage rate. The coverage rates are calculated for 20 randomly selected Si particles, and their average value is calculated.
[0034] The Si particles may be entirely composed of silicon, or may contain components other than silicon, such as silicon monoxide (SiO). The proportion of silicon in the Si particles is, for example, 50 mass % or more, and may be 100 mass %.
[0035] The Si particles may contain at least one component selected from the group consisting of diamond, amorphous carbon, zirconium oxide, aluminum oxide, and yttrium oxide. When diamond is contained, the bond inside the silicon is strengthened. When an oxide such as aluminum oxide is contained, the oxide is located at the interface between the silicon particle and the silicon dioxide film, and the bond between the two can be strengthened. When amorphous carbon is contained, the stress of expansion and contraction of the Si particles is easily alleviated. The above component may be contained inside the Si particle, or a part of the above component may be exposed on the surface of the Si particle. The content of the above component is, for example, 0.5% by mass or more and 5% by mass or less with respect to the entire Si particle containing the above component.
[0036] The content of the flaky Si particles in the negative electrode mixture layer may be 20% by mass or more and 94% by mass or less with respect to the entire negative electrode mixture layer. When the content of the flaky Si particles in the negative electrode mixture layer is 20% by mass or more with respect to the entire negative electrode mixture layer, it is easy to increase the capacity. When the content of the flaky Si particles in the negative electrode mixture layer is 94% by mass or less with respect to the entire negative electrode mixture layer, it is possible to sufficiently contain the binder and the conductive agent, and it is easy to obtain the effect of improving the cycle characteristics by the flaky Si particles and the silicate.
[0037] When the negative electrode mixture layer contains a carbon material as a conductive agent, the content of the flaky Si particles in the negative electrode mixture layer can be determined, for example, by the following method.
[0038] A part of the negative electrode mixture layer is taken to obtain a sample, which is then completely dissolved in a heated acid solution (e.g., a mixture of hydrofluoric acid and nitric acid), and the carbon residue is removed by filtration to obtain a sample solution. The obtained sample solution is analyzed by inductively coupled plasma atomic emission spectroscopy (ICP-AES) to determine the total amount of Si in the sample. The amount of silicate in the sample, determined by the method described below, is converted to the amount of Si derived from silicate. The amount of Si particles is determined by subtracting the amount of Si derived from silicate from the total amount of Si.
[0039] (Silicate) Si particles expand and contract greatly during charging and discharging. By including silicate in the negative electrode mixture layer, the adhesion between the Si particles in the negative electrode mixture layer and between the negative electrode mixture layer and the negative electrode current collector is improved, and the isolation of Si particles due to the expansion and contraction of Si particles and the increase in contact resistance between the negative electrode mixture layer and the negative electrode current collector are suppressed.
[0040] The silicate preferably contains an alkali metal salt, and more preferably contains at least one selected from the group consisting of sodium silicate, potassium silicate, and lithium silicate. The water resistance of the coating is Li>K>Na, and the adhesion is Na>K>Li, and from the viewpoint of the balance between the two, potassium silicate is particularly preferred.
[0041] The alkali metal salt of silicic acid may have a composition represented by, for example, M2O·nSiO2 (element M is an alkali metal element, and n is the molar ratio of SiO2 to M2O). The alkali metal element M preferably includes at least one selected from the group consisting of lithium (Li), sodium (Na), and potassium (K). Sodium silicate is represented by Na2O·nSiO2, where n is, for example, 0.5 to 4.0. Potassium silicate is represented by K2O·nSiO2, where n is, for example, 1.0 to 5.0. Lithium silicate is represented by Li2O·nSiO2, where n is, for example, 2.0 to 10.
[0042] In other words, the silicate preferably contains silicon dioxide (SiO2) and an oxide of an alkali metal element M (M2O). The silicate may further contain an oxide of a Group 2 element. The oxide of the Group 2 element may, for example, contain at least one selected from the group consisting of BeO, MgO, CaO, SrO, and BaO. The silicate may further contain other components such as Al2O3, B2O3, P2O5, and ZrO2.
[0043] The content of silicate in the negative electrode mixture layer may be 3% by mass or more and 20% by mass or less with respect to the entire negative electrode mixture layer. When the content of silicate in the negative electrode mixture layer is 3% by mass or more with respect to the entire negative electrode mixture layer, the effect of improving the binding property by the silicate is easily obtained. When the content of silicate in the negative electrode mixture layer is 20% by mass or less with respect to the entire negative electrode mixture layer, the flaky Si particles can be sufficiently contained in the negative electrode mixture layer, and the effect of improving the cycle characteristics by the silicate and the flaky Si particles is easily obtained.
[0044] When the negative electrode mixture layer contains a silicate and a carbon material, and the silicate is an alkali metal salt, the content of the silicate in the negative electrode mixture layer can be determined, for example, by the following method.
[0045] A part of the negative electrode mixture layer is taken to obtain a sample, which is then completely dissolved in a heated acid solution (e.g., hydrochloric acid), and the carbon residue is removed by filtration to obtain a sample solution. The obtained sample solution is then analyzed by inductively coupled plasma atomic emission spectroscopy (ICP-AES) to determine the amount of alkali metal element M in the sample. The obtained amount of alkali metal element M is converted into the amount of silicate (M2O·nSiO) that is determined later.
[0046] The composition of the silicate can be determined, for example, by the following method.
[0047] The battery is disassembled, the negative electrode is removed, washed with a non-aqueous solvent such as ethylene carbonate, and dried, and then the cross-section of the negative electrode mixture layer is processed using a cross-section polisher (CP) to obtain a sample. A field emission scanning electron microscope (FE-SEM) is used to obtain a backscattered electron image of the sample cross-section, and the silicate particles are observed. An Auger electron spectroscopy (AES) analyzer is used to perform elemental analysis of a certain region in the center of the observed silicate particles, and the silicate composition is determined.
[0048] For example, if the silicate is an alkali metal salt, determine the amounts of silicon and alkali metal element M. Assuming that all of the alkali metal element M is the oxide MO, convert the amount of M obtained in the above analysis to the amount of MO. Assuming that all of the Si is SiO2, convert the amount of Si obtained in the above analysis to the amount of SiO. Calculate the n value of MO·nSiO based on the amounts of MO and SiO2 obtained above. Repeat the same analysis for the 10 silicate particles observed and calculate the average n value.
[0049] (Conductive agent) Silicon particles have a lower electrical conductivity than carbon materials, which will be described later. By incorporating a conductive agent into the negative electrode mixture layer, the electrical conductivity between the silicon particles in the negative electrode mixture layer and between the negative electrode mixture layer and the negative electrode current collector is improved. The conductive network between the silicon particles is maintained during repeated charging and discharging, and isolation of the silicon particles due to expansion and contraction is suppressed.
[0050] As the conductive agent, it is preferable to use a carbon material having electrical conductivity. It may be a carbon material capable of electrochemically absorbing and releasing lithium ions. Examples of such carbon materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Graphite means a material having a graphite-type crystal structure, and includes, for example, natural graphite, artificial graphite, expanded graphite, graphitized mesophase carbon particles, and the like.
[0051] Among them, graphite is more preferable, and flake graphite is even more preferable, because it is chargeable and dischargeable, conductive, and has a shape similar to that of flake silicon particles, so that it is easy to maintain conductive contacts. Graphite has high conductivity and excellent charge / discharge stability. In addition, graphite has a smaller irreversible capacity than flake silicon particles, and the volume change due to expansion and contraction is also small.
[0052] As the conductive carbon material, carbons such as acetylene black and ketjen black, and carbon fibers such as carbon nanotubes may be used.
[0053] The content of the conductive agent in the negative electrode mixture layer may be 3% by mass or more and 60% by mass or less with respect to the entire negative electrode mixture layer. When the content of the conductive agent in the negative electrode mixture layer is 3% by mass or more with respect to the entire negative electrode mixture layer, the effect of improving the conductivity by the conductive agent is easily obtained. When the content of the conductive agent in the negative electrode mixture layer is 60% by mass or less with respect to the entire negative electrode mixture layer, the flaky Si particles and silicate can be sufficiently contained in the negative electrode mixture layer, and the effect of improving the cycle characteristics by the flaky Si particles and silicate is easily obtained.
[0054] When the conductive agent is a carbon material, the content of the conductive agent in the negative electrode mixture layer can be determined, for example, by the following method.
[0055] A part of the negative electrode mixture layer is taken to obtain a sample, which is dissolved in an acid such as hydrochloric acid and then filtered through a membrane filter of 0.5 μm or less, and the filtered residue is dried at 100° C. for at least 1 hour. After measuring the mass of the dried product, the carbon content is measured using a combustion-type carbon concentration meter (non-dispersive infrared absorption method).
[0056] 2 is a cross-sectional view that illustrates an example of a negative electrode for a nonaqueous electrolyte secondary battery according to an embodiment of the present disclosure. The X direction in FIG. 2 indicates the thickness direction of the negative electrode mixture layer 12 (the first mixture layer 12a and the second mixture layer 12b) (the direction perpendicular to the main surface of the negative electrode current collector 11).
[0057] The negative electrode 10 includes a negative electrode current collector 11 and a negative electrode mixture layer 12 supported on both sides of the negative electrode current collector 11. As shown in FIG. 2, the negative electrode mixture layer 12 may include a first mixture layer 12a disposed on the surface of the negative electrode current collector 11 and a second mixture layer 12b covering the surface of the first mixture layer 12a. The first mixture layer 12a includes flaky Si particles. The second mixture layer 12b includes a binder and a conductive agent. The second mixture layer 12b is a layer that does not include flaky Si particles. It is preferable that the first mixture layer 12a further includes a binder and a conductive agent. In FIG. 2, the negative electrode mixture layer 12 is formed on both sides of the negative electrode current collector 11, but the negative electrode mixture layer may be formed on one surface of the negative electrode current collector.
[0058] Here, FIG. 3 is an enlarged cross-sectional view of the Y portion of the negative electrode 10 in FIG. 2. The Y portion shows a part of the first mixture layer and the negative electrode current collector. The X direction in FIG. 3 shows the thickness direction of the first mixture layer 12a in FIG. 2. In the first mixture layer 12a, a plurality of flaky Si particles 13 are filled so as to be stacked in the X direction. The thickness direction of the flaky Si particles 13 faces the X direction. Small gaps 14 between the Si particles 13 are likely to be formed in the surface direction of the negative electrode mixture layer 12 (first mixture layer 12a). It is preferable that silicate or silicate and a conductive agent are present in the gaps 14.
[0059] As the Si particles expand and contract during charging and discharging, voids are likely to form between the Si particles, particularly on the surface of the negative electrode mixture layer, and the Si particles are likely to come into contact with the non-aqueous electrolyte. By covering the first mixture layer with the second mixture layer, side reactions caused by contact between the Si particles and the non-aqueous electrolyte are suppressed, and erosion deterioration of the Si particles caused by excessive film formation on the Si particle surfaces is suppressed.
[0060] Since the silicate and conductive agent in the second mixture layer have good lithium ion conductivity and electron conductivity, even if the first mixture layer is covered to some extent with the second mixture layer, the absorption and release of lithium ions by the Si particles is smoothly performed. The second mixture layer only needs to cover the surface of the first mixture layer to such an extent that contact between the surface of the first mixture layer and the nonaqueous electrolyte is suppressed, and may be sufficiently thinner than the first mixture layer.
[0061] The thickness T1 of the first mixture layer 12a is, for example, not less than 1 μm and not more than 100 μm. The thickness T2 of the second mixture layer 12b is, for example, not less than 0.1 μm and not more than 5 μm.
[0062] The thickness T1 of the first mixture layer 12a and the thickness T2 of the second mixture layer 12b are determined, for example, by the following method.
[0063] A cross section in the thickness direction of the negative electrode mixture layer (a cross section perpendicular to the main surface of the negative electrode current collector) is observed by SEM, and element mapping is performed by energy dispersive X-ray (EDX) analysis to obtain the distribution of Si elements. The thicknesses of 10 arbitrary points in the region where Si elements are abundant are measured, and the average value is calculated to obtain the thickness T1 of the first mixture layer. The thicknesses of 10 arbitrary points in the region where Si elements are few are measured, and the average value is calculated to obtain the thickness T2 of the second mixture layer.
[0064] [Method of manufacturing a negative electrode for a non-aqueous electrolyte secondary battery] A method for manufacturing a negative electrode for a non-aqueous electrolyte secondary battery according to an embodiment of the present disclosure includes a first step of obtaining a first slurry, a second step of obtaining a second slurry, a third step of forming a first coating film using the first slurry, and a fourth step of forming a second coating film using the second slurry. The first slurry includes an organic dispersion medium and flaky Si particles dispersed in the organic dispersion medium. The second slurry includes a silicate as a binder, a conductive agent, and water. In the third step, the first slurry is applied to the surface of a negative electrode current collector to form a first coating film including flaky Si particles. In the fourth step, the second slurry is applied to the surface of the first coating film to form a second coating film including a silicate and a conductive agent.
[0065] (1st step) In the first slurry, the Si particles are dispersed in an organic dispersion medium, which prevents the Si particles from coming into contact with air. The organic dispersion medium may be an alcohol such as methanol, ethanol, or isopropyl alcohol, or n-hexane or acetone.
[0066] In the first step, it is preferable to disperse the raw silicon in an organic dispersion medium and wet-pulverize the mixture to obtain a first slurry. A bead mill or a ball mill is used for the wet-pulverization. For example, the raw silicon and the organic dispersion medium are put into a pot, a plurality of beads or balls are placed in the pot, the lid is closed, and the pot is rotated to perform the pulverization process. For example, a cylindrical container made of stainless steel is used as the pot. For example, beads or balls made of tungsten carbide, stainless steel, alumina, or zirconia are used as the beads or balls.
[0067] A dispersion of flake-shaped Si particles obtained by wet grinding can be directly applied to the negative electrode current collector to form a film containing flake-shaped Si particles. This eliminates the need for processes such as drying the Si particles to remove the dispersion medium or washing them, which is advantageous in terms of production cost and productivity. Until the Si particles are filled into the negative electrode current collector, contact between the Si particles and air is suppressed, making it easier to maintain the quality of the Si particles.
[0068] The size and aspect ratio of the flaky Si particles can be adjusted, for example, by the size and number of beads or balls, the rotation speed of the pot, the grinding time, etc. The above wet grinding may be carried out in an inert atmosphere.
[0069] During the wet grinding, a silicon dioxide film can be formed on the surface of the flake-shaped Si particles. The silicon dioxide film has good lithium ion conductivity and can be used as a protective film for the Si particles without being removed. This eliminates the need for a carbon coating process or an oxide film removal process, which is advantageous in terms of production cost and productivity.
[0070] As the raw silicon, for example, silicon particles obtained by pulverizing high-purity silicon ingots used in solar cells and semiconductors with a jet mill or the like can be used. In addition, for example, silicon cutting chips (cuttings) discarded during the manufacturing process of silicon wafers used in solar cells and semiconductor devices can be used. In this case, it is advantageous in terms of cost. Silicon cutting chips are discharged during the cutting process of crystalline silicon ingots. Fixed abrasive wires (diamond wires, etc.) are used for the cutting process. When cutting chips are used, the cutting chips themselves are flat and are easily converted into amorphous silicon after being pulverized with a bead mill or the like, which is likely to contribute to improving the characteristics. In addition, spherical silicon particles may be used as the raw silicon.
[0071] The silicon cutting waste may be used as is without cleaning (removing components other than Si that adhere during the ingot cutting process). Depending on the components other than Si contained in the silicon cutting waste, the cycle characteristics may improve. For example, carbon present on the surface of silicon particles can improve the cycle characteristics by mitigating the expansion and contraction of silicon particles.
[0072] (2nd process) In the second step, water is added to the silicate and the conductive agent, and the mixture is stirred to obtain a second slurry. It is preferable to use an alkali metal salt of silicic acid as the silicate and graphite as the conductive agent. In the second slurry, the silicate is dissolved in water. This makes it easy for the particle surfaces of the hydrophilic active material and conductive agent to be covered with the silicate, and for the silicate to easily penetrate into the voids in the first coating film. The second slurry makes it easy to obtain excellent binding properties throughout the negative electrode.
[0073] (3rd step) In the third step, the first slurry is applied onto the surface of the negative electrode current collector to form a first coating film containing flaky Si particles.
[0074] The first slurry is applied using a coating device such as a bar coater, a blade coater, a roll coater, a comma coater, a die coater, or a lip coater. In the case of the coating device exemplified above, the flake-shaped Si particles can be easily filled on the negative electrode current collector so that the Si particles are piled up in the thickness direction of the first coating film. In addition, the thickness of the first coating film can be easily controlled.
[0075] (4th step) In the fourth step, a second slurry is applied onto the first coating film to form a second coating film containing silicate and a conductive agent. In the fourth step, a part of the second slurry (silicate and conductive agent) may be included in the first coating film. That is, a part of the second slurry may be filled into the gaps between the Si particles in the first coating film. In the fourth step, most of the second slurry (silicate and conductive agent) may be filled into the gaps between the Si particles in the first coating film to form a thin second coating film. If the first coating film repels the second slurry and the second slurry is difficult to apply, a surfactant may be added.
[0076] The second slurry is applied using a coating device such as a bar coater, a blade coater, a roll coater, a comma coater, a die coater, a lip coater, etc. In the case of the coating devices exemplified above, a part of the second slurry is likely to fill the gaps between the Si particles in the first mixture layer.
[0077] From the viewpoint of preventing contact between the first coating (Si particles) and water, it is preferable to dry the second coating promptly after application of the second slurry.
[0078] After the first slurry is applied, the first coating film is dried. After the second slurry is applied, the second coating film is dried. If necessary, the first and second coating films after drying may be compressed (rolled). The first coating film may be dried before the second slurry is applied, or may be dried after the second slurry is applied and at the same time as the second coating film is dried. If the first coating film is dried before the second slurry is applied, a portion of the second slurry is likely to fill the gaps between the Si particles in the first coating film when the second slurry is applied.
[0079] The first and second mixture layers are formed by drying the first and second coating films or by compressing them after drying. The first mixture layer is formed from the first slurry, and may be formed from the first and second slurries. That is, the first mixture layer is a layer containing Si particles and may further contain silicate and a conductive agent. The second mixture layer is a layer formed from the second slurry, does not contain Si particles, and contains silicate and a conductive agent.
[0080] [Nonaqueous electrolyte secondary battery] The nonaqueous electrolyte secondary battery according to the embodiment of the present disclosure includes a positive electrode, a negative electrode, and a nonaqueous electrolyte, and the negative electrode includes the above-described negative electrode mixture layer.
[0081] [Negative electrode] The negative electrode includes a negative electrode current collector and a negative electrode mixture layer supported on the surface of the negative electrode current collector. The negative electrode mixture layer may be formed by preparing a negative electrode slurry containing a negative electrode active material, a binder, a conductive agent, and a dispersion medium, applying the negative electrode slurry to the surface of the negative electrode current collector, and drying the slurry. The coating film after drying may be compressed as necessary. The negative electrode mixture layer including a first mixture layer and a second mixture layer may be formed by the above-mentioned method for producing a negative electrode. The negative electrode mixture layer may be formed on one surface or both surfaces of the negative electrode current collector.
[0082] (Negative electrode active material) The negative electrode active material includes at least flaky Si particles, and may further include other materials other than the flaky Si particles. Examples of the negative electrode active material other than the flaky Si particles include carbon materials that can electrochemically absorb and release lithium ions. From the viewpoint of increasing capacity, the proportion of the flaky Si particles in the negative electrode active material is preferably 80 mass% or more, more preferably 100 mass%.
[0083] The binder contains at least a silicate and may further contain other materials besides the silicate. From the viewpoint of improving cycle characteristics, the ratio of the silicate in the binder is preferably 80 mass % or more, and more preferably 100 mass %.
[0084] Examples of binders other than silicates include resin materials, for example, fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resin; polyimide resins such as polyimide and polyamideimide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymer; vinyl resins such as polyvinyl acetate; and rubber-like materials such as styrene-butadiene copolymer rubber (SBR).
[0085] Examples of binders that can be used other than silicates include carboxymethylcellulose (CMC) and its modified products (including salts such as Na salts), cellulose derivatives such as methylcellulose (cellulose ethers, etc.), and saponified polymers having vinyl acetate units such as polyvinyl alcohol. One type of binder may be used alone, or two or more types may be used in combination.
[0086] The conductive agent preferably contains the above carbon material, more preferably graphite. From the viewpoint of improving cycle characteristics, the ratio of the carbon material in the conductive agent is preferably 80 mass % or more, more preferably 100 mass %. As the conductive agent, in addition to the above carbon material, metal powder such as aluminum, metal fiber, etc. may be used. The conductive agent may be used alone or in combination of two or more kinds.
[0087] Examples of the dispersion medium for the negative electrode slurry include water, alcohol such as ethanol, ether such as tetrahydrofuran, amide such as dimethylformamide, and N-methyl-2-pyrrolidone (NMP). The dispersion medium may be used alone or in combination of two or more. Alcohol contains chemically active oxygen, which moderately oxidizes silicon and contributes to improving characteristics, but n-hexane does not contain oxygen and contributes little to improving characteristics.
[0088] (Negative electrode current collector) As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc. The thickness of the negative electrode current collector is not particularly limited, but is preferably 1 to 50 μm, more preferably 5 to 20 μm, from the viewpoint of the balance between the strength and weight reduction of the negative electrode.
[0089] The surface roughness (arithmetic mean roughness) Ra of the metal foil used for the negative electrode current collector is preferably 0.5 μm or more and 5 μm or less. The arithmetic mean roughness Ra is determined in accordance with JIS B 0601 (2013).
[0090] When the surface roughness Ra of the metal foil is 0.5 μm or more, good adhesion between the negative electrode mixture layer and the metal foil during charging and discharging is likely to be firmly maintained. The detailed reason is unclear, but it is speculated as follows. Since the flake-shaped Si particles are packed so as to be stacked in the thickness direction of the negative electrode mixture layer, the stress caused by the expansion and contraction of the Si particles is larger in the surface direction than in the thickness direction of the negative electrode mixture layer. When the Ra is 0.5 μm or more, the stress in the surface direction of the negative electrode mixture layer caused by the expansion and contraction of the Si particles near the metal foil is likely to be received by the convex parts of the metal foil surface, and the stress applied to the interface between the negative electrode mixture layer and the metal foil is likely to be alleviated. In addition, when the surface roughness Ra of the metal foil is 5 μm or less, an anchor effect due to the unevenness is generated, and the adhesion to the negative electrode mixture layer is improved.
[0091] [Positive electrode] The positive electrode includes, for example, a positive electrode current collector and a positive electrode mixture layer supported on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry in which the positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it. The coating film after drying may be compressed as necessary. The positive electrode mixture layer may be formed on one surface of the sheet-shaped positive electrode current collector or on both surfaces. The positive electrode mixture includes a positive electrode active material as an essential component, and may include a binder, a conductive agent, etc. as optional components. NMP or the like is used as the dispersion medium of the positive electrode slurry.
[0092] As the positive electrode active material, for example, a composite oxide containing lithium and a transition metal is used. Examples of the transition metal include Ni, Co, and Mn. Examples of the composite oxide containing lithium and a transition metal include Li a CoO2, Li a NiO2, Li a MnO2, Li a Co b Ni 1-b O2, Li a Co b Me 1-b O c , Li a Ni 1-b Meb O c 、 Li a Mn2O4, Li a Mn 2-b Me b O 4、 LiMePO 4、 Li2MePO4F (Me is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B). Here, a = 0 to 1.2, b = 0 to 0.9, and c = 2.0 to 2.3. Note that the a value indicating the molar ratio of lithium is the value immediately after the production of the active material and increases or decreases during charge and discharge.
[0093] Among them, Li a Ni b Me 1-b O2 (Me is at least one selected from the group consisting of Mn, Co, Al, Fe, Ti, Sr, and B, 0 < a ≤ 1.2, and 0.3 ≤ b ≤ 1).) is preferred. From the viewpoint of increasing the capacity, it is more preferable to satisfy 0.85 ≤ b ≤ 1. From the viewpoint of the stability of the crystal structure, Li a Ni b Co c Al d O2 (0 < a ≤ 1.2, 0.85 ≤ b < 1, 0 < c < 0.15, 0 < d ≤ 0.1, b + c + d = 1) is even more preferred.
[0094] As the binder and the conductive agent, the same ones as those exemplified for the negative electrode can be used.
[0095] The shape and thickness of the positive electrode current collector can be selected from the shapes and ranges according to the negative electrode current collector, respectively. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, etc.
[0096] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the non-aqueous electrolyte is preferably, for example, 0.5 mol / L or more and 2 mol / L or less. By setting the lithium salt concentration within the above range, a non-aqueous electrolyte having excellent ion conductivity and appropriate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.
[0097] Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, cyclic carboxylates, and chain carboxylates. Examples of the cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of the chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of the cyclic carboxylates include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Examples of the chain carboxylates include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. The non-aqueous solvent may be used alone or in combination of two or more.
[0098] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10, lithium aliphatic carboxylates, LiCl, LiBr, LiI, borates, imide salts, etc. Examples of borates include lithium bis(1,2-benzenediolate(2-)-O,O')borate, lithium bis(2,3-naphthalenediolate(2-)-O,O')borate, lithium bis(2,2'-biphenyldiolate(2-)-O,O')borate, lithium bis(5-fluoro-2-oleate-1-benzenesulfonic acid-O,O')borate, etc. Examples of imide salts include lithium bisfluorosulfonylimide (LiN(FSO2)2), lithium bistrifluoromethanesulfonate imide (LiN(CF3SO2)2), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF3SO2)(C4F9SO2)), and lithium bispentafluoroethanesulfonate imide (LiN(C2F5SO2)2). The lithium salt may be used alone or in combination of two or more. The concentration of the lithium salt in the nonaqueous electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less. The lithium salt may be used alone or in combination of two or more.
[0099] [Separator] Usually, it is desirable to interpose a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.
[0100] An example of the structure of the non-aqueous electrolyte secondary battery is a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and a non-aqueous electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, an electrode group of another form, such as a stacked type electrode group formed by stacking a positive electrode and a negative electrode with a separator interposed therebetween, may be applied. The non-aqueous electrolyte secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, a laminate type, or the like.
[0101] Hereinafter, as an example of the nonaqueous electrolyte secondary battery according to the present disclosure, the structure of a prismatic nonaqueous electrolyte secondary battery will be described with reference to Fig. 1. Fig. 1 is a schematic perspective view of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure, with a portion cut away.
[0102] The battery includes a bottomed rectangular battery case 4, and an electrode group 1 and an electrolyte solution housed within the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, positive electrode, and separator around a flat plate-shaped winding core and then removing the winding core.
[0103] One end of the negative electrode lead 3 is attached to the negative electrode collector of the negative electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6 provided on the sealing plate 5 via a resin insulating plate. The negative electrode terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the positive electrode lead 2 is connected to the back surface of the sealing plate 5 via an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive electrode terminal. The insulating plate separates the electrode group 1 and the sealing plate 5, and separates the negative electrode lead 3 and the battery case 4. The periphery of the sealing plate 5 is fitted into the open end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed with the sealing plate 5. The electrolyte injection hole provided in sealing plate 5 is closed with a plug 8 .
[0104] <Example> Examples of the present disclosure will be specifically described below, but the present invention is not limited to the following examples.
[0105] Example 1 [Preparation of first slurry] Raw material silicon was dispersed in an organic dispersion medium and wet-pulverized to obtain a first slurry in which flake-shaped Si particles were dispersed in the organic dispersion medium (first step).
[0106] The raw silicon used was silicon used in the manufacturing process of silicon wafers, which was ground in a jet mill. Isopropyl alcohol was used as the organic dispersion medium. A bead mill device (LMZ015, manufactured by Aizawa Finetech Co., Ltd.) was used for wet grinding. 75 g of raw silicon and 425 g of organic dispersion medium were placed in a pot, followed by 0.5 kg of zirconia beads (diameter 0.3 mm) and closing the lid (filling rate 90%), and grinding was carried out for 1 hour in an inert atmosphere. The peripheral speed was 14 m / s and the flow rate was 0.5 L / min. A screen with an opening of 0.1 mm was used.
[0107] [Preparation of second slurry] After adding water to the binder and conductive agent, the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to obtain a second slurry (second process). As the binder, potassium silicate (K2O·nSiO2) powder (n=3) was used. As the conductive agent, acetylene black (AB) powder (Denka Black Li100, manufactured by Denka, average particle size (D50) 35 nm) was used. The mass ratio of the binder to the conductive agent was 1:1.
[0108] [Preparation of negative electrode] The first slurry was applied to the surface of copper foil (thickness 10 μm) as a negative electrode current collector, the first coating was dried, the second slurry was applied to the surface of the first coating, and the second coating was dried (third and fourth steps). The first and second coatings after drying were compressed. In this manner, a first mixture layer containing Si particles and a second mixture layer (a layer not containing Si particles) containing silicate and a conductive agent were formed in this order on both sides of the copper foil to obtain a negative electrode. The first mixture layer further contained silicate and a conductive agent derived from the second slurry. The amount of the second slurry applied was 1 cm per unit area of the copper foil. 2 The total mass of silicate and conductive agent filled per unit area of copper foil is 1 cm 2The mass of the Si particles was adjusted to be 2 / 8 of the mass of the Si particles filled per negative electrode mixture layer. That is, the content of the Si particles in the negative electrode mixture layer (the sum of the first mixture layer and the second mixture layer) was 80 mass% with respect to the entire negative electrode mixture layer. The content of the silicate in the negative electrode mixture layer was 10 mass% with respect to the entire negative electrode mixture layer. The content of AB in the negative electrode mixture layer was 10 mass% with respect to the entire negative electrode mixture layer.
[0109] The thickness T1 of the first mixture layer and the thickness T2 of the second mixture layer obtained by the above-mentioned method were 20 μm and 1 μm, respectively. The cross section of the negative electrode mixture layer (first mixture layer) was observed by SEM. Fine flake-shaped Si particles were filled so as to be piled up in the thickness direction of the negative electrode mixture layer.
[0110] The thickness T of the flaky Si particles determined by the method described above was 100 nm. The long diameter LD of the flaky Si particles determined by the method described above was 1000 nm. The ratio of (long diameter LD / thickness T) was 10. The thickness of the silicon dioxide film on the surface of the flaky Si particles determined by the method described above was 9 nm.
[0111] [Preparation of positive electrode] N-methyl-2-pyrrolidone (NMP) was added to the positive electrode mixture, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a positive electrode slurry. 0.8 Co 0.18 Al 0.02 A mixture of acetylene black (a conductive agent) and polyvinylidene fluoride (a binder) (mass ratio 95:2.5:2.5) was used. The positive electrode slurry was then applied to the surface of an aluminum foil (thickness 20 μm), the coating was dried, and then compressed to form a positive electrode mixture layer on both sides of the aluminum foil, thereby obtaining a positive electrode.
[0112] [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte was prepared by dissolving a lithium salt in a non-aqueous solvent. The non-aqueous solvent was a mixed solvent (volume ratio 3:7) of ethylene carbonate (EC) and dimethyl carbonate (DMC). LiPF6 was used as the lithium salt, and the concentration of LiPF6 in the non-aqueous electrolyte was 1.0 mol / L.
[0113] [Preparation of non-aqueous electrolyte secondary battery] A tab was attached to each electrode, and the positive and negative electrodes were spirally wound with a separator between them so that the tabs were located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an exterior body made of an aluminum laminate film and vacuum dried at 105°C for 2 hours. After that, a nonaqueous electrolyte was injected and the opening of the exterior body was sealed to obtain a battery A1.
[0114] The batteries prepared as above were evaluated as follows.
[0115] [Rating 1: Initial charge capacity] Each battery was charged at 25° C. with a constant current of 1 It (800 mA) until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 1 / 20 It (40 mA), to determine the initial charge capacity. The initial charge capacity was expressed as an index with the initial charge capacity of battery B1 of Comparative Example 1 taken as 100.
[0116] [Evaluation 2: Capacity retention at 100 cycles] The battery was repeatedly charged and discharged under the following conditions.
[0117] <Charging> At 25° C., constant current charging was performed at a current of 1 It (800 mA) until the voltage reached 4.2 V, and then constant voltage charging was performed at a voltage of 4.2 V until the current reached 1 / 20 It (40 mA).
[0118] <Discharge> At 25° C., constant current discharge was performed at a current of 1 It (800 mA) until the voltage reached 2.75 V.
[0119] The rest period between charging and discharging was 10 minutes. The ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 1st cycle was taken as the capacity retention rate, and was expressed as an index with the capacity retention rate of battery B1 of Comparative Example 1 taken as 100.
[0120] Example 2 Battery A2 of Example 2 was produced and evaluated in the same manner as Battery A1 of Example 1, except that in the preparation of the first slurry, powder obtained by cleaning silicon from cutting chips generated during the manufacturing process of silicon wafers was used as raw silicon. The thickness of the silicon dioxide film on the surface of the flaky Si particles determined by the above-mentioned method was 10 nm.
[0121] Example 3 In the preparation of the first slurry, silicon powder obtained by cleaning silicon from cutting chips generated during the manufacturing process of silicon wafers was used as raw silicon. In the preparation of the second slurry, graphite (Graphite UP-5α, manufactured by Nippon Graphite Co., Ltd.) was used as the conductive agent instead of AB. Except for the above, the battery A3 of Example 3 was prepared and evaluated in the same manner as the battery A1 of Example 1. The thickness of the silicon dioxide film on the surface of the flake-shaped Si particles determined by the above-mentioned method was 8 nm.
[0122] Comparative Example 1 In the preparation of the first slurry, the raw silicon was a powder with an average particle size of 10 μm, which was obtained by pulverizing silicon used in the manufacturing process of silicon wafers with a jet mill, and n-hexane was used as the organic dispersion medium. The peripheral speed was 18 m / s and the flow rate was 0.75 L / min.
[0123] In preparing the second slurry, water was added to the conductive agent without adding a binder, and then the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation).
[0124] Except for the above, battery B1 of Comparative Example 1 was produced and evaluated in the same manner as battery A1 of Example 1. The Si particles had a nearly spherical shape with a particle size of about 30 nm.
[0125] Comparative Example 2 In the preparation of the first slurry, the raw silicon was a powder with an average particle size of 10 μm, which was obtained by pulverizing silicon used in the manufacture of silicon wafers using a jet mill, and n-hexane was used as the organic dispersion medium. The peripheral speed was 18 m / s, and the flow rate was 0.75 L / min.
[0126] Except for the above, a battery B2 of Comparative Example 2 was produced in the same manner as the battery A1 of Example 1 and evaluated.
[0127] Comparative Example 3 In preparing the first slurry, powder having an average particle size of 10 μm obtained by pulverizing silicon used in the manufacture of silicon wafers using a jet mill was used as the raw silicon, and n-hexane was used as the organic dispersion medium.
[0128] In preparing the second slurry, sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) were used as binders instead of potassium silicate.
[0129] Except for the above, a battery B3 of Comparative Example 3 was produced in the same manner as the battery A1 of Example 1 and evaluated.
[0130] Comparative Example 4 In preparing the first slurry, powder having an average particle size of 10 μm obtained by pulverizing silicon used in the manufacture of silicon wafers using a jet mill was used as the raw silicon, and n-hexane was used as the organic dispersion medium.
[0131] In preparing the second slurry, CMC-Na was used as the binder instead of silicate.
[0132] Except for the above, a battery B4 of Comparative Example 4 was produced in the same manner as the battery A1 of Example 1 and evaluated.
[0133] [Table 1]
[0134] The batteries A1 to A3 of Examples 1 to 3 had higher initial charge capacities and improved cycle characteristics compared to the batteries B1 to B4 of Comparative Examples 1 to 4. The batteries A2 and A3 of Examples 2 and 3 had higher initial charge capacities and further improved cycle characteristics. [Industrial Applicability]
[0135] The nonaqueous electrolyte secondary battery according to the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like. [Explanation of symbols]
[0136] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing 10 negative electrode 11 Negative electrode current collector 12 Negative electrode mixture layer 12a First mixture layer 12b Second mixture layer 13,20 Flake-shaped Si particles 14 void
Claims
1. a negative electrode current collector; and a negative electrode mixture layer supported on the negative electrode current collector, the negative electrode mixture layer includes a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, a binder, and a conductive agent; The negative electrode active material contains flaky silicon particles, The negative electrode for a non-aqueous electrolyte secondary battery, wherein the binder contains a silicate.
2. The thickness T of the silicon particle is 30 nm or more and 250 nm or less, and 2. The negative electrode for a nonaqueous electrolyte secondary battery according to claim 1, wherein the silicon particles have a long diameter LD of 500 nm or more and 5000 nm or less.
3. 3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein at least a portion of the surface of said silicon particle is covered with a film of silicon dioxide.
4. 4. The negative electrode for a non-aqueous electrolyte secondary battery in accordance with claim 3, wherein the thickness of the silicon dioxide film is 2 nm or more and 50 nm or less.
5. 5. The negative electrode for a nonaqueous electrolyte secondary battery according to claim 1, wherein in a dark-field image of the silicon particle taken with a transmission electron microscope, a ratio of an area of a white portion indicating crystals to an area of the silicon particle is 20% or less.
6. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5, wherein the silicon particles contain at least one component selected from the group consisting of diamond, amorphous carbon, zirconium oxide, aluminum oxide, and yttrium oxide.
7. 7. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the silicate comprises at least one selected from the group consisting of potassium silicate, sodium silicate, and lithium silicate.
8. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 7, wherein the conductive agent contains graphite.
9. The negative electrode for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 8, wherein the content of the silicon particles in the negative electrode mixture layer is 20 mass% or more and 94 mass% or less with respect to the entire negative electrode mixture layer.
10. The negative electrode for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 9, wherein the content of the silicate in the negative electrode mixture layer is 3 mass% or more and 20 mass% or less with respect to the entire negative electrode mixture layer.
11. The negative electrode for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 10, wherein the content of the conductive agent in the negative electrode mixture layer is 3 mass% or more and 60 mass% or less with respect to the entire negative electrode mixture layer.
12. the negative electrode mixture layer has a first mixture layer disposed on a surface of the negative electrode current collector and a second mixture layer covering a surface of the first mixture layer, The first mixture layer includes the silicon particles, the silicate, and the conductive agent, 10. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the second mixture layer contains the silicate and the conductive agent.
13. The negative electrode current collector includes a metal foil, 13. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the metal foil has a surface roughness Ra of 0.5 μm or more and 5 μm or less.
14. A positive electrode, a negative electrode, and a non-aqueous electrolyte, The negative electrode of any one of claims 1 to 13, wherein the negative electrode is a non-aqueous electrolyte secondary battery.
15. A first step of obtaining a first slurry including an organic dispersion medium and flaky silicon particles dispersed in the organic dispersion medium; A second step of obtaining a second slurry containing a silicate as a binder, a conductive agent, and water; a third step of applying the first slurry to a surface of a negative electrode current collector to form a first coating film containing the silicon particles; a fourth step of applying the second slurry onto a surface of the first coating film to form a second coating film containing the silicate and the conductive agent; The method for producing a negative electrode for a non-aqueous electrolyte secondary battery includes the steps of:
16. 16. The method for producing a negative electrode for a nonaqueous electrolyte secondary battery according to claim 15, wherein in the first step, raw material silicon is dispersed in the organic dispersion medium and wet-pulverized to obtain the first slurry.
17. 17. The method for producing a negative electrode for a nonaqueous electrolyte secondary battery according to claim 15, wherein in the fourth step, a part of the second slurry is impregnated into the first coating film.
18. The method for producing a negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 15 to 17, wherein the silicate includes an alkali metal salt.
19. The method for producing a negative electrode for a nonaqueous electrolyte secondary battery according to any one of claims 15 to 18, wherein the conductive agent contains graphite.
Citation Information
Patent Citations
Silicon positive electrode for rechargeable battery (secondary battery)
JP2013140820A
Skeleton-forming agent, electrode arranged by use thereof, and manufacturing method of electrode
JP2018063912A
Skeleton forming agent and negative electrode using the same
JP2018085276A
Steel foil and method for producing same
WO2013157600A1
Negative electrode material for lithium ion batteries, lithium ion battery, method and apparatus for producing negative electrode for lithium ion batteries, and method and apparatus for producing negative electrode material for lithium ion batteries
WO2015189926A1